2022
DOI: 10.3389/fphar.2022.919974
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness analyses of pharmacological treatments in heart failure

Abstract: In a rapidly growing and aging population, heart failure (HF) has become recognised as a public health concern that imposes high economic and societal costs worldwide. HF management stems from the use of highly cost-effective angiotensin converting enzyme inhibitors (ACEi) and β-blockers to the use of newer drugs such as sodium-glucose cotransporter-2 inhibitors (SGLT2i), ivabradine, and vericiguat. Modelling studies of pharmacological treatments that report on cost effectiveness in HF is important in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…were not yet part of standard OMT [17,18] . Furthermore, the Swedish Coronary Angiography and Angioplasty registry (SCAAR) [19] evaluated long-term outcomes in patients with ischemic heart failure with LVEF < 50% who underwent either PCI or CABG.…”
Section: Treatment Of Cad With Reduced Lvefmentioning
confidence: 99%
“…were not yet part of standard OMT [17,18] . Furthermore, the Swedish Coronary Angiography and Angioplasty registry (SCAAR) [19] evaluated long-term outcomes in patients with ischemic heart failure with LVEF < 50% who underwent either PCI or CABG.…”
Section: Treatment Of Cad With Reduced Lvefmentioning
confidence: 99%
“…Evidence-based medicine has found that sodium, glucose cotransporter 2 inhibitor (SGLT2i), sacubitril/valsartan (SAC/ VAL), ivabradine, vericiguat and omecamtiv may show considerable benefits for HFrEF (Lim et al, 2022), but HFpEF remains an important unmet field and effective treatment for patients remains unsolved. Empagliflozin and dapagliflozin have become the preferred drugs that have provided potential benefits to patients with HFpEF in recent years (Anker et al, 2021;Solomon et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Cost-effectiveness analysis is useful to examine costs and health outcomes of one or more interventions, by comparing one intervention with another (or to the standard of care) and approximating the costs required to gain a unit of a health outcome as a life year gained or a death prevented. 8 Therefore, cost-effectiveness helps identify ways to redirect economic resources by demonstrating not only the benefit of allocating them to effective interventions but also the utility of choosing more costeffective interventions. 8 The analysis was performed according to China's health care perspective.…”
mentioning
confidence: 99%
“…8 Therefore, cost-effectiveness helps identify ways to redirect economic resources by demonstrating not only the benefit of allocating them to effective interventions but also the utility of choosing more costeffective interventions. 8 The analysis was performed according to China's health care perspective. 7 As the first step, the authors conducted a meta-analysis, pooling the results of 6 pivotal studies in the field.…”
mentioning
confidence: 99%
See 1 more Smart Citation